The development of Inverter Fuzzy Logic Control for Induction Motor Control by Vector Control Method in Electric Vehicle - Purwanto, Era; Ashary, Mohammad; Subagio, Subagio; Purnomo, Mauridhi Heri (UI Scholars Hub, 2008)
The development of Inverter Fuzzy Logic Control for Induction Motor Control by Vector Control Method in Electric Vehicle. In response to concerns about energy cost, energy dependence, and environmental damage, a rekindling of interest in electric vehicles (EV’s) has been obvious. Thus, the development of power electronics technology for EV’s will take an accelerated pace to fulfill the market needs, regarding with the problem in this paper is presented development of fuzzy logic inverter in induction motor control for electric vehicle propulsion. The Fuzzy logic inverter is developed in this system to directed toward developing an improved propulsion system for electric vehicles applications, the fuzzy logic controller is used for switching process. This paper is describes the design concepts, configuration, controller for inverter fuzzy logic and drive system is developed for this high-performance electric vehicle.